Penerapan Problem Based Learning (PBL) dengan Media Audiovisual untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPS 2 SMAN 1 Wonosobo Mata Pelajaran Ekonomi - Nazila Kurniati; Kristiani Kristiani; Leny Noviani (Departement of Mathematics Education, 2023)
This research was conducted with the aim of improving student learning outcomes through the application of the PBL learning model with audiovisual media in class XI IPS 2 SMAN 1 Wonosobo in Economics. This research is a classroom action research. Sources of research data include events, informants, and documents. Data collection techniques were carried out by participatory observation, in-depth interviews, documentation studies, and evaluation/tests, with data validation test techniques, namely triangulation. Data analysis was performed using descriptive comparative statistical techniques and critical analysis techniques. The results of this study, namely, the post test results for pre-action with student learning completeness of 39.39% with a class average value of 59.73. After implementing the action, the completeness of student learning outcomes in the post test cycle I was 75.76% with an average class score of 68.48 and cycle II of 90.91% with an average class score of 80.61. Based on the results of the research that has been done, it can be concluded that the application of PBL with audiovisual media can improve student learning outcomes in class XI IPS 2 SMAN 1 Wonosobo.